Pengaruh Pertumbuhan Penjualan, Leverage, dan Kompetensi Komisaris Independent terhadap penghindaran pajak - Ariesta, Priscilla Gareen; Purwaningsih, Eny (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Because of the advancement of the globalization era and the international trade economy, domestic taxpayers frequently invest some of their capital abroad. This study aims to examine and determine the effect of sales growth, debt levels, and the competence of independent commissioners on tax evasion, both partially and simultaneously, in property and real estate companies listed on the Indonesia Stock Exchange in the 2016–2020 period. Research uses the causal type to determine the relationship between cause and effect for two or more variables. There are 12 companies for 5 years that meet the research sample criteria, so the sample used is 36 financial statements. Partially, this research has found a positive effect of the sales growth variable on tax evasion; the leverage variable has a negative effect on tax evasion; and the independent commissioner's competence variable has no effect on tax evasion. However, simultaneously, the variables of sales growth, debt levels, and independent commissioners have an influence on tax evasion.